Novel Immunohistochemical Techniques Using Discrete Signal Amplification Systems for Human Cutaneous Peripheral Nerve Fiber Imaging - Wang, Ningshan (SAGE Publications, 2011)
Confocal imaging uses immunohistochemical binding of specific antibodies to visualize tissues, but technical obstacles limit more widespread use of this technique in the imaging of peripheral nerve tissue. These obstacles include same-species antibody cross-reactivity and weak fluorescent signals of individual and co-localized antigens. The aims of this study were to develop new immunohistochemical techniques for imaging of peripheral nerve fibers. Three-millimeter punch skin biopsies of healthy individuals were fixed, frozen, and cut into 50-µm sections. Tissues were stained with a variety of antibody combinations with two signal amplification systems, streptavidin-biotin-fluorochrome (sABC) and tyramide-horseradish peroxidase-fluorochrome (TSA), used simultaneously to augment immunohistochemical signals. The combination of the TSA and sABC amplification systems provided the first successful co-localization of sympathetic adrenergic and sympathetic cholinergic nerve fibers in cutaneous human sweat glands and vasomotor and pilomotor systems. Primary antibodies from the same species were amplified individually without cross-reactivity or elevated background interference. The confocal fluorescent signal-to-noise ratio increased, and image clarity improved. These modifications to signal amplification systems have the potential for widespread use in the study of human neural tissues.